Describing Picture Technique in Improving Students' Speaking Skill at the Second Grade of SMP Swasta Taruna Karya Kupang in the school year 2023/2024: English - Fanggidae, Yennsy Mervilen; Isu, Rudolof (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
This study entitled "Describing Picture Technique in Improving Students' Speaking Skill at The Second Grade of SMP Swasta Taruna Karya Kupang in the school year 2023/2024. It was conducted to know the ability level of the second-grade students of SMP Taruna Kupang in the school year 2023/2024 in English speaking ability to identify the difficulties encountered by the second-grade students of SMP Taruna Kupang in the school year 2023/2024 in English speaking ability. In this research, the writer used descriptive method. It was used to describe the ability of the second-grade students of SMP Taruna Kupang in the school year 2023/2024 in writing the English-speaking ability and to describe the difficulties encountered by the second-grade students of SMP Taruna Kupang in the school year 2023/2024 in English speaking ability. The population of this study was the second-grade students of SMP Taruna Kupang in the school that consist of 30 students and the writer took sample trough random sample. The ability of the second-grade students of SMP Taruna Kupang in the school year 2023/2024 in English speaking ability with the percentage of excellent level was 40%, very good level 33,33%, good level 20%, and fair level 6,66%. From the percentage above it proved that the students the second-grade students of SMP Swasta Taruna Karya Kupang in the school year 2023/2024 were included into excellent level, because the percentage of excellent level was the highest then it followed by very good level, good level and the last was fair level. Therefore. The second semester students of SMP Swasta Taruna Karya Kupang had improved trough described picture with direct method.